2018
DOI: 10.1089/dna.2018.4264
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAGAS5Suppresses 3T3-L1 Cells Adipogenesis Through miR-21a-5p/PTEN Signal Pathway

Abstract: Emerging studies indicated that both long noncoding RNAs and micro-RNAs play crucial roles in the mediation of adipogenesis, which is closely linked to obesity-related diseases. However, the mechanisms of lncRNA-miRNAs coregulating in adipogenesis are still largely unknown. In this study, we determined that lncRNA growth arrest-specific 5 (GAS5) presented an opposite expression pattern with miR-21a-5p in 3T3-L1 adipocytes development. To explore the role of GAS5 in adipogenesis, pcDNA3.1-GAS5 expression vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Moreover, our differentiation was conducted at 100% confluence. Our data agreed well with the published data (Coccia et al, 1992;Liu et al, 2018).…”
Section: Identification Of Lncrnas That Significantly Changed Expresssupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, our differentiation was conducted at 100% confluence. Our data agreed well with the published data (Coccia et al, 1992;Liu et al, 2018).…”
Section: Identification Of Lncrnas That Significantly Changed Expresssupporting
confidence: 93%
“…Chen et al (2017) found that overexpression of U90926 remarkably inhibits 3T3-L1 preadipocyte differentiation. Another lncRNA, growth arrest-specific 5, or Gas5, was reported that its expression level increases along with the adipocyte differentiation after 24 to 96 hours of induction in 3T3-L1 cells and high cell density during culture also induces its expression (Coccia et al, 1992;Liu et al, 2018). We observed that Gas5 expression increased by 1.56-fold with FDR 0.3% after 2 days of differentiation.…”
Section: Identification Of Lncrnas That Significantly Changed Expressmentioning
confidence: 54%
See 2 more Smart Citations
“…miR-624-3p, miR-130a, and miR-21 (40)(41)(42). There are several potential binding sites of miR-21 on the PTEN 3'UTR, such as GAUAAG and UCUG*UG*GCUA (43,44). PTEN is an inhibitor of the PI3K/Akt signaling pathway (45), and the PTEN/Akt axis is a pivotal regulatory pathway in IR-induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%